Effect of extender-additives on motility, viability and acrosomal integrity of triple bred (HF x J x K) bulls' spermatozoa during cryopreservation - RAVAL, RUPESH J; DHAMI, A J; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
An investigation was undertaken on 36 semen ejaculates of 4 mature triplebred (HF x J x· Kankrej) bulls, to study the effect of extender-additives, viz. cysteine HCI (0.1 %) and EDTA (0.1 %)in Tris fructose yolk glycerol diluent using split-sample technique (I : 10 dilution). The motility, viabilityand acrosome integrity of spermatozoa during cryopreservation was recorded. The data analyzed using 3-factors' factorial CRD revealed that there were significant (P < 0.01) differences in percentages of motile and live sperms and intact acrosomes between bulls, freezing stages and additives. Amongthe two- and three-way interactions of bulls, stages and additives studied, only bull x stage and/or bull x additive interactions were found significant (P < 0.05) for these traits. The mean percentages ofprogressively motile spermatozoa at initial, prefreeze and post-thaw stages in control Tris diluentwere 77.92 ± 0.73, 76.11 ± 0.75 and 46.39 ± 1.27, respectively; in presence ofEDTA 83.20 ± 0.67,81.39 ± 0.84 and 53.19 ± 1.26, and in presence of cysteine 82.08 ± 0.85, 79.86 ± 1.04 and 52.22 ± 1.20, respectively. The corresponding values for live sperm percent were 87.98 ± 0.67, 83.83 ± 0.73 and 57.22 ± 1.09 in control Tris diluent; 89.89 ± 0.55, 85.72 ± 0.73 and 61.50 ± 0.76 with EDTA, and89.65 ± 0.69, 84.17 ± 0.81 and 57.17 ± 1.25 with cysteine, respectively. The mean percentages of sperms with intact acrosome at initial, prefreeze and post-thaw stages in plain Tris diluent were 91.25± 0.43, 88.44 ± 0.35 and 81.42 ± 0.44, respectively. The corresponding values with EDTA were 93.23± 0.35, 91.22 ± 0.38 and 85.08 ± 0.39, and that with cysteine 92.26 ± 0.39, 90.17 ± 0.39 and 84.44 ±0.35, respectively. The trend observed for the effect of freezing steps and additives was identical inthe semen of all 4 individual bulls for motile, live sperm and intact acrosome. In general, the valuesof all three traits were higher (P=0.05) at all stages of cryofreezing of semen in the presence of EDT A and cysteine hydrochloride (EDTA being superior to cysteine) as compared to control i.e. Tris diluent, and hence could be recommended for their routine use on bovine semen stations.
Keywords: Extender-additives; Cryopreservation; Triplebred bulls; Motility; Viability; Acrosome integrity